Productive and reproductive performance of cows reared under organic vis-à-vis conventional management system in West Bengal - SHANDILYA, S K; CHATTERJEE, A; ROY, P K (The Indian Journal of Animal Sciences, 2015)
The study was conducted on 24 Jersey × Tharparkar / Red Sindhi cows maintained at the Institute farm to find the impact of organic dairy farming on milk production, milk composition and reproductive performance of cows and compared with the performance of cows reared under conventional management system. Cows under first year organic production management system (OPMS) had significantly higher yield than the performance of cows under third year OPMS. The differences between first and second year and between second and third year performance was not significant. There was a decrease in milk production in the second year and thereafter reduction rate was very low in the third year. Production and reproduction traits were not affected by the management systems (organic and conventional). The 3-year performance data revealed that the 305-day milk yield was slightly higher for cows maintained under conventional management system than the performance of cows maintained under organic management system (2,488.75 kg vs. 2,392.47 kg). Reproductive performance was better in the organic group than the conventional group. The cows maintained under organic management system had significantly higher fat % (5.25±0.08%) than the cows maintained under conventional management system (4.72±0.11%). Significantly higher protein% was observed for the cows maintained under conventional management system (3.76±0.04%) as compared to the cows maintained under organic management system (3.28±0.03%). The cows under organic management had lower SNF % and higher total solid % than the cows maintained under conventional management. However, the differences were statistically nonsignificant. The results indicated better reproductive performance and higher fat % in organically managed cows than conventional.